Attapulgite composite solid waste-based aerogel material as well as preparation method and application thereof

By using fly ash, alkaline industrial solid waste and industrial waste salt and combining concave and concave rod soil as reinforcement materials, the concave and concave rod soil composite solid waste-based aerogel material is prepared, which solves the problems of high preparation cost and insufficient strength of existing aerogel materials, and achieves efficient adsorption and high-value utilization of solid waste.

CN119565559APending Publication Date: 2025-03-07NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411857573.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing silica aerogel materials have high preparation costs and insufficient strength of the gel system, which affects its adsorption performance and cycle stability.

Method used

Fly ash, alkaline industrial solid waste and industrial waste salt are used as raw materials, and a concave and convex rod soil composite solid waste-based aerogel material is prepared by mixing grinding, calcining, acid leaching and sol-gel processes, combined with concave and convex rod soil as reinforcement materials.

Benefits of technology

The preparation cost of aerogel materials is reduced, the skeleton strength and adsorption performance stability of the gel are improved, and the efficient adsorption of various pollutants and the high-value utilization of solid waste is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565559A_ABST
    Figure CN119565559A_ABST
Patent Text Reader

Abstract

The invention discloses an attapulgite composite solid waste-based aerogel material as well as a preparation method and application thereof, and the attapulgite composite solid waste-based aerogel material is prepared by taking fly ash, alkaline industrial solid waste and the like as raw materials and attapulgite as a reinforcing material through sol-gel, surface hydrophobic modification and supercritical drying. The density is relatively low, the porosity is relatively high, and the hydrophobic and oleophylic properties are strong. Meanwhile, by doping the attapulgite, not only can the synergistic adsorption performance of the attapulgite and the aerogel be exerted, but also the skeleton strength of the aerogel can be enhanced, so that the cyclic adsorption stability of the aerogel is improved. The adsorbing material also has the advantages of mild and controllable preparation process, low toxicity of the product, environmental friendliness and the like, a new scheme is provided for adsorbing VOCs in waste gas in a complex industrial environment, and high-valued utilization of various bulk solid wastes is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aerogel materials, and specifically relates to an attapulgite composite solid waste-based aerogel material and a preparation method and application thereof. Background Art

[0002] Silica aerogel is widely used in thermal insulation, drug carrier, catalyst carrier, organic adsorption, cosmic dust capture and other fields due to its high specific surface area, low thermal conductivity, high porosity, low dielectric constant and excellent adsorption performance. At present, conventional silica aerogel is prepared by sol-gel combined with supercritical drying of organic silicon sources such as tetraethyl orthosilicate (TEOS) and tetramethyl silicate (TMOS). Due to the high price of organic silicon sources, the complex supercritical drying process and the high difficulty of high-quality silica aerogel technology, the price of silica aerogel is relatively high, which hinders the promotion and application of aerogel in the industrial field. Therefore, using industrial solid waste with high silicon and aluminum content to replace expensive organic silicon sources to prepare aerogel materials has become an inevitable trend in current aerogel research and has important practical significance.

[0003] Fly ash is an industrial waste discharged from thermal power plants. Fly ash contains a large amount of silicon and aluminum elements. Research on the preparation of aerogel using fly ash as raw material has made significant progress. However, current research on the preparation of aerogel from fly ash often involves mixing fly ash with alkaline chemical reagents such as sodium carbonate and sodium hydroxide, and then extracting SiO2 and Al2O3 sols through high-temperature calcination, acid leaching, sol-gel and other processes to further prepare aerogel materials. In this process, a large amount of strong alkaline reagents such as sodium carbonate and sodium hydroxide are consumed, which increases the manufacturing cost of solid waste-based aerogel materials. Using highly alkaline solid waste materials to replace alkaline chemical reagents such as sodium carbonate and sodium hydroxide can not only significantly reduce the manufacturing cost of solid waste-based aerogels, reduce resource waste and environmental pollution, but also help to further improve the high-value utilization of industrial solid waste.

[0004] Since the SiO2 and Al2O3 composite sol dissolved from fly ash is not easy to form a stable three-dimensional network structure during gelation, the gel system is not strong enough. When used to adsorb pollutants, the network structure is prone to collapse, affecting its cyclic adsorption stability, thus limiting the application of solid waste-based aerogels in the adsorption field. Summary of the invention

[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing all-solid waste-based aerogel materials using bulk solid waste as raw materials in view of the shortcomings of the prior art, so as to achieve high-value utilization of bulk solid waste.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing an attapulgite composite solid waste-based aerogel material comprises the following steps: (1) Fly ash, alkaline industrial solid waste and industrial waste salt are mixed and fully ground to obtain mixed solid waste powder; (2) using a tablet press to press the mixed solid waste powder obtained in step (1) into blocks under a certain pressure, calcining at a high temperature of 700° C. to 900° C. for 1 to 4 hours, and cooling naturally after calcination; (3) Grinding the calcined material again, then mixing it with the acid solution and stirring it evenly, mixing the filtrate obtained by filtration with attapulgite until the solution shows obvious wall adhesion and then standing to gel; (4) curing the gel obtained in step (3) in an oven, then washing with deionized water until the color of the aqueous solution does not change significantly, and then washing with anhydrous ethanol to remove impurities in the gel and replace the deionized water; (5) performing surface hydrophobic modification on the gel washed in step (4) to obtain a surface hydrophobic gel; (6) Drying the gel after surface hydrophobic modification in step (5) to obtain the gel.

[0007] Specifically, in step (1), the alkaline industrial solid waste is at least one of steel slag, alkali slag and red mud; and the main component of the industrial waste salt is sodium chloride and / or sodium carbonate.

[0008] Specifically, in step (1), the fly ash, alkaline industrial solid waste and industrial waste salt are mixed in a mass ratio of (5-10): (4-15): (0.5-2), and then ground by a vibration mill for 10-30 seconds, which is repeated 2-3 times.

[0009] Specifically, in step (1), the tableting pressure is set to 15 MPa-20 MPa.

[0010] Specifically, in step (3), the grinding time is 10-30s, and it is repeated 2-3 times; then, a hydrochloric acid aqueous solution with a concentration of 3mol / L-6mol / L is used to fully stir for 20-40min, and the filtrate obtained by filtering is mixed with the attapulgite by mechanical stirring or ultrasonic stirring.

[0011] The present invention directly uses attapulgite as an additional material, and does not need to be pretreated. It is directly added into the sol to form a composite gel, and the process is simple. The strong acidity of the sol under acid leaching conditions is fully utilized to modify the surface of the attapulgite, thereby improving the adsorption performance of the attapulgite; the synergistic adsorption effect of aerogel and attapulgite is brought into play, and efficient adsorption of multiple pollutants is achieved at the same time; the attapulgite is used as a skeleton reinforcement material to improve the skeleton strength of the aerogel and improve the stability of the aerogel adsorption performance.

[0012] Specifically, in step (3), the mass ratio of the material obtained by grinding again to the hydrochloric acid aqueous solution and attapulgite is (2-10): (10-60): (0.1-5).

[0013] Specifically, in step (4), the temperature in the oven is controlled at 50-60°C, and the time is controlled at 10-12 hours; deionized water 2-5 times the volume of the gel is used to wash the gel each time, and it is replaced every 2-6 hours; anhydrous ethanol 2-5 times the volume of the gel is used to wash the gel each time, and it is replaced every 10-12 hours. During the solvent replacement process, the gel is sealed and stored in the oven.

[0014] Specifically, in step (5), the surface hydrophobic modification is carried out using a mixed solution of trimethylchlorosilane and ethanol, the mass ratio of trimethylchlorosilane to ethanol is 0.5-1.5:10, the volume ratio of the mixed solution to the gel is 2-4:1, and the gel is immersed in the mixed solution for 6-24 hours for surface hydrophobic modification.

[0015] Specifically, in step (6), the drying method is any one of CO2 supercritical drying, ethanol supercritical drying, vacuum drying, and freeze drying.

[0016] Furthermore, the attapulgite composite solid waste-based aerogel material prepared by the above preparation method is also within the protection scope required by the present invention, and the obtained aerogel material has a nanoporous network structure.

[0017] Furthermore, the present invention also claims to protect the use of the above-mentioned aerogel material as a thermal insulation material or a harmful gas adsorption material.

[0018] The present invention makes full use of the composition and physicochemical properties of various solid wastes, utilizes the alkalinity of industrial solid wastes to replace chemical reagents such as NaOH and Na2CO3, and coordinates the use of effective elements such as Si and Al in various solid wastes to achieve high-value utilization of various solid wastes. The Si, Al, Na and other elements in solid wastes are comprehensively utilized, the use of chemical reagents such as NaOH and Na2CO3 is avoided, and activation is performed based on the alkalinity of the solid waste itself, thereby reducing the preparation cost of solid waste-based aerogels. Beneficial Effects

[0019] (1) In the present invention, attapulgite is a natural one-dimensional nanomaterial with needle-shaped, rod-shaped or fibrous crystals and good adsorption, catalytic and thermal stability. Modifying attapulgite in an acidic environment based on the sol to remove impurities and organic matter therein helps to improve the adsorption performance of attapulgite. At the same time, attapulgite is used to improve the connection strength of the aerogel skeleton and the structural stability of the aerogel skeleton to form a solid waste-based aerogel with stable adsorption performance. The present invention prepares solid waste-based aerogels with stable structural properties based on the physical and chemical properties of different solid wastes, realizes the high-value utilization of various solid wastes, and has important scientific significance and application prospects.

[0020] (2) The solid waste-based composite aerogel prepared by the present invention using fly ash, alkaline industrial solid waste, etc. as raw materials and attapulgite as reinforcing material through sol-gel, surface hydrophobic modification and supercritical drying has low density, high porosity, and strong hydrophobic and lipophilic properties. At the same time, the addition of attapulgite can not only exert the synergistic adsorption performance of attapulgite and aerogel, but also enhance the skeleton strength of aerogel, thereby improving its cyclic adsorption stability. The adsorption material also has the advantages of mild and controllable preparation process, low product toxicity, and environmental friendliness. It provides a new solution for the adsorption of VOCs in waste gas under complex industrial environments, and realizes the high-value utilization of various bulk solid wastes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0022] Figure 1 This is a physical photo of the composite aerogel material prepared in Example 1.

[0023] Figure 2 This is a microscopic morphology of the composite aerogel material prepared in Example 1.

[0024] Figure 3 This is a relationship diagram between the saturated adsorption capacity of the composite aerogel material for n-hexane and the number of adsorption and desorption cycles in Example 1.

[0025] Figure 4 N2 adsorption-desorption curves of the composite aerogel adsorption materials prepared in various embodiments. DETAILED DESCRIPTION

[0026] The present invention can be better understood with reference to the following examples.

[0027] In the following examples, fly ash comes from a power company in Shandong, and the main components of the fly ash are 31.2% Al2O3, 61.3% SiO2 and 4.4% CaO.

[0028] The steel slag comes from a steel enterprise in Anhui Province. The main components of the steel slag are 6.9% Al2O3, 10.5% SiO2, 5.8% MgO, 44.6% CaO and 16.65% Fe2O3.

[0029] The red mud comes from an aluminum chemical enterprise in Shandong. The main components of the red mud are 25.6% Al2O3, 17.9% SiO2, 14.1% Na2O, 0.7% CaO, and 36.3% Fe2O3.

[0030] The waste salt comes from a chemical enterprise in Tai'an. The main components of the waste salt are 89.4% NaCl, 0.6% SiO2, and 6.9% NaNO3.

[0031] The attapulgite comes from a company in Xuyi. The main components of the attapulgite are 11.1% Al2O3, 47.6% SiO2, 0.2% Na2O, 8.1% MgO, 7.6% CaO and 7% Fe2O3. Example 1

[0032] Fly ash was mixed with steel slag, red mud and waste salt in a mass ratio of 10:5:5:2, and the material was ground twice with a vibration mill, each time for 30 seconds. The tablet press pressure was adjusted to 18 MPa, and the ground material was pressed into a rectangular block of about 5 cm*5 cm*3 cm, placed in a muffle furnace and calcined at 750°C for 2.5 hours, and naturally cooled to obtain the alkali-fused material.

[0033] The alkali-fused material was ground twice using a vibration mill, each time for 20 seconds. 5 mol / L hydrochloric acid was used to dissolve the effective elements such as Si, Al, and Na in the material under mechanical stirring conditions. The mass ratio of the material to the hydrochloric acid was 1:8, and the stirring time was 20 minutes. Then, the filtrate was obtained by suction filtration, and attapulgite was slowly added to the filtrate. The mass ratio of the material to the attapulgite was 10:1. Ultrasonic stirring was performed until the solution was observed to have obvious wall hanging phenomenon and then the gel was allowed to stand.

[0034] The gel was placed in an oven at 50°C for 12 hours, and then soaked and washed 5 times with deionized water 5 times the volume of the gel, and the deionized water was replaced every 4 hours to remove the impurity ions in the gel. Then, anhydrous ethanol 5 times the volume of the gel was used to replace the water in the gel and remove the impurities in the gel, and the anhydrous ethanol was replaced every 12 hours, and repeated 3 times. The gel after impurity removal was subjected to surface hydrophobic modification using a mixed solution of trimethylchlorosilane and ethanol, and the mass ratio of trimethylchlorosilane to ethanol was controlled to be 1:10, and the surface hydrophobic modification time was 12 hours.

[0035] The hydrophobically modified gel is dried using CO2 supercritical drying to obtain a attapulgite composite solid waste-based aerogel having a nanoporous network structure.

[0036] The specific surface area of ​​the attapulgite composite solid waste-based aerogel material prepared in this example is 740.32 m 2 / g, the saturated adsorption capacity for ethanol, n-hexane, isopropanol, and dimethylformamide solutions are 11.36g / g, 8.42g / g, 14.73g / g, and 15.01g / g, respectively. Taking n-hexane as the adsorption object, after saturated adsorption at room temperature, it is desorbed in a 105℃ oven. After 10 cycles of adsorption and desorption, the saturated adsorption capacity retention rate is 91.37%. See the physical and microscopic pictures of the sample for details. Figure 1 and Figure 2 The relationship between the aerogel adsorption capacity retention rate and the number of cyclic adsorption and desorption times is shown in Figure 3 The aerogel adsorption material described in this embodiment is solid particles with rich pore structure. Example 2

[0037] Fly ash was mixed with steel slag, red mud and waste salt in a mass ratio of 10:3:8:1, and the material was ground twice with a vibration mill, each time for 30 seconds. The tablet press pressure was adjusted to 15 MPa, and the ground material was pressed into a rectangular block of about 5 cm*5 cm*3 cm, placed in a muffle furnace and calcined at 800°C for 2 hours, and naturally cooled to obtain the alkali-fused material.

[0038] The above alkali-fused material was ground twice using a vibration mill, each time for 20 seconds. 6 mol / L hydrochloric acid was used to dissolve the effective elements such as Si, Al, and Na in the material under mechanical stirring conditions. The mass ratio of the material to hydrochloric acid was 1:7, and the stirring time was 20 minutes. Then, suction filtration was performed, and attapulgite was slowly added to the filtrate. The mass ratio of the material to attapulgite was 5:1. Ultrasonic stirring was performed until the solution was observed to have obvious wall hanging phenomenon and then the gel was allowed to stand.

[0039] The gel was placed in an oven at 50°C for 12 hours, and then soaked and washed 8 times with deionized water 3 times the volume of the gel, and the deionized water was replaced every 2 hours to remove the impurity ions in the gel. Then, anhydrous ethanol 4 times the volume of the gel was used to replace the water in the gel and remove the impurities in the gel, and the anhydrous ethanol was replaced every 12 hours, and repeated 3 times. The gel after impurity removal was subjected to surface hydrophobic modification using a mixed solution of trimethylchlorosilane and ethanol, and the mass ratio of trimethylchlorosilane to ethanol was controlled to be 1:10, and the surface hydrophobic modification time was 10 hours.

[0040] The hydrophobically modified gel is dried using CO2 supercritical drying to obtain a attapulgite composite solid waste-based aerogel having a nanoporous network structure.

[0041] The specific surface area of ​​the attapulgite composite solid waste-based aerogel material prepared in this example is 672.81 m2 / g, the saturated adsorption capacities for ethanol, n-hexane, isopropanol and dimethylformamide solutions are 10.55g / g, 7.62g / g, 12.34g / g and 11.86g / g respectively. Taking n-hexane as the adsorption object, after saturated adsorption at room temperature, it is desorbed in a 105℃ oven. After 10 cycles of adsorption and desorption, the saturated adsorption capacity retention rate is 93.86%. Example 3

[0042] Fly ash was mixed with steel slag, red mud and waste salt in a mass ratio of 10:8:2:4, and the material was ground twice with a vibration mill, each time for 30 seconds. The tablet press pressure was adjusted to 20 MPa, and the ground material was pressed into a rectangular block of about 5 cm*5 cm*3 cm, placed in a muffle furnace and calcined at 700°C for 4 hours, and naturally cooled to obtain the alkali-fused material.

[0043] The alkali-fused material was ground twice using a vibration mill, each time for 20 seconds. 4 mol / L hydrochloric acid was used to dissolve the effective elements such as Si, Al, and Na in the material under mechanical stirring conditions. The mass ratio of the material to the hydrochloric acid was 1:10, and the stirring time was 20 minutes. Then, the filtrate was filtered, and attapulgite was slowly added to the filtrate. The mass ratio of the material to the attapulgite was 3:1. Ultrasonic stirring was performed until the solution was observed to have obvious wall hanging phenomenon and then allowed to stand for gelation.

[0044] The gel was placed in an oven at 50°C for 12 hours, and then soaked and washed 6 times with deionized water 4 times the volume of the gel, and the deionized water was replaced every 3 hours to remove the impurity ions in the gel. Then, anhydrous ethanol 2 times the volume of the gel was used to replace the water in the gel and remove the impurities in the gel, and the anhydrous ethanol was replaced every 12 hours, and repeated 4 times. The gel after impurity removal was subjected to surface hydrophobic modification using a mixed solution of trimethylchlorosilane and ethanol, the mass ratio of trimethylchlorosilane to ethanol was 1:10, and the surface hydrophobic modification time was 10 hours.

[0045] The hydrophobically modified gel is dried using CO2 supercritical drying to obtain a attapulgite composite solid waste-based aerogel having a nanoporous network structure.

[0046] The specific surface area of ​​the attapulgite composite solid waste-based aerogel material prepared in this example is 643.48 m 2 / g, the saturated adsorption capacities for ethanol, n-hexane, isopropanol and dimethylformamide solutions are 10.39g / g, 6.34g / g, 9.83g / g and 10.38g / g respectively. Taking n-hexane as the adsorption object, after saturated adsorption at room temperature, it is desorbed in a 105℃ oven. After 10 cycles of adsorption and desorption, the saturated adsorption capacity retention rate is 95.92%.

[0047] The N2 adsorption-desorption curves of the aerogels prepared in Example 1, Example 2 and Example 3 are shown in the attached Figure 4 .

[0048] The present invention provides a concept and method for a attapulgite composite all-solid waste-based aerogel adsorption material. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.

Claims

1. A method for preparing an attapulgite composite solid waste-based aerogel material, characterized in that: The steps include: (1) Fly ash, alkaline industrial solid waste and industrial waste salt are mixed and fully ground to obtain mixed solid waste powder; (2) calcining the mixed solid waste powder obtained in step (1) at a high temperature of 700° C. to 900° C. for 1 to 4 hours, and cooling naturally after calcination; (3) Grinding the calcined material again, then mixing it with the acid solution and stirring it evenly, and mixing the filtrate obtained by filtration with attapulgite until the solution shows a wall hanging phenomenon and then standing to gel; (4) curing the gel obtained in step (3) in an oven, then washing with deionized water until the color of the aqueous solution does not change significantly, and then washing with anhydrous ethanol to remove impurities in the gel and replace the deionized water; (5) performing surface hydrophobic modification on the gel washed in step (4) to obtain a surface hydrophobic gel; (6) Drying the gel after surface hydrophobic modification in step (5) to obtain the gel.

2. The method for preparing the attapulgite composite solid waste-based aerogel material according to claim 1, characterized in that: In step (1), the alkaline industrial solid waste is at least one of steel slag, alkali slag and red mud; and the main component of the industrial waste salt is sodium chloride and / or sodium carbonate.

3. The method for preparing the attapulgite composite solid waste-based aerogel material according to claim 1, characterized in that: In step (1), the fly ash, alkaline industrial solid waste and industrial waste salt are mixed in a mass ratio of (5-10): (4-15): (0.5-2), and then ground by a vibration mill for 10-30 seconds, which is repeated 2-3 times.

4. The method for preparing the attapulgite composite solid waste-based aerogel material according to claim 1, characterized in that: In step (3), the grinding time is 10-30s, and it is repeated 2-3 times; then, a hydrochloric acid aqueous solution with a concentration of 3mol / L-6mol / L is used to fully stir for 20-40min, and the filtrate obtained by filtering is mixed with the attapulgite by mechanical stirring or ultrasonic stirring.

5. The method for preparing the attapulgite composite solid waste-based aerogel material according to claim 1, characterized in that: In step (3), the mass ratio of the material obtained by grinding again to the hydrochloric acid solution and attapulgite is (2-10): (10-60): (0.1-5).

6. The method for preparing the attapulgite composite solid waste-based aerogel material according to claim 1, characterized in that: In step (4), the temperature in the oven is controlled at 50-60°C and the time is controlled at 10-12 hours; the gel is washed with deionized water 2-5 times the volume of the gel each time and replaced every 2-6 hours; the gel is washed with anhydrous ethanol 2-5 times the volume of the gel each time and replaced every 10-12 hours.

7. The method for preparing the attapulgite composite solid waste-based aerogel material according to claim 1, characterized in that: In step (5), the surface hydrophobic modification is carried out using a mixed solution of trimethylchlorosilane and ethanol, the mass ratio of trimethylchlorosilane to ethanol is 0.5-1.5:10, the volume ratio of the mixed solution to the gel is 2-4:1, and the gel is immersed in the mixed solution for surface hydrophobic modification for 6-24 hours.

8. The method for preparing the attapulgite composite solid waste-based aerogel material according to claim 1, characterized in that: In step (6), the drying method is any one of CO2 supercritical drying, ethanol supercritical drying, vacuum drying, and freeze drying.

9. The attapulgite composite solid waste-based aerogel material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the aerogel material according to claim 9 as a thermal insulation material or a harmful gas adsorption material.